Associations between alcohol consumption patterns and attitudes towards alcohol interlocks. (November 2017) - Bishop, Caitlin A.; Liu, Sara; Stephens, Amanda N.; Fitzharris, Michael
Highlights: One-fifth of 2994 participants stated they had driven whilst they suspected they were over the legal limit. Half of the sample agreed that an alcohol interlock would be personally useful. 74% of high-risk drinkers stated that an alcohol interlock would be of use personally. The majority of participants agreed that drink-drive offenders should be mandated to have an alcohol interlock fitted upon relicensing. Participants supported a requirement for offenders to undertake clinical interventions prior to and upon re-licensing. Abstract: Background: Drink-driving and alcohol-related crashes are a significant problem globally. Alcohol interlocks are used to prevent drivers with a blood alcohol concentration above a pre-determined level from starting their vehicle, making the technology highly effective in preventing drink-drive episodes. While alcohol interlocks are commonly used in drink-drive offender groups, their broader use as a preventative road safety strategy is considered increasingly feasible. In this context it is important to understand attitudes towards the technology, and to investigate whether these attitudes vary according to alcohol consumption patterns as this influences the acceptability of a broad-based preventative alcohol interlock program. Methods: A representative sample of 2994 Australian drivers participated in an online cross-sectional survey. Participants reported their alcohol consumption, drink-drive behaviour and attitudes towards the use of alcohol interlocks for personal use and for drink-drive offenders. Results: Half of the sample stated that alcohol interlocks would be of use personally. Seventy-four percent of high-risk drinkers (defined by an AUDIT score ≥20) stated they would find the technology personally useful when compared to 49% of low-risk drinkers (AUDIT ≤7). Overwhelmingly, more than 80% of participants agreed with the mandatory instalment of alcohol interlocks and compulsory clinical interventions for drink-drive offenders, with more low-risk drinkers supporting this than the high-risk drinkers. Conclusions: While there were mixed opinions regarding the perceived personal usefulness of alcohol interlocks, higher-risk drinkers were most likely to perceive interlocks as being of use for themselves. This high-risk group however, was less likely to provide support for clinical interventions and additional re-licensing requirements aimed at eliciting changes in drinking behaviour. These findings have important implications for drink-drive offender relicensing and the likely success of drink-driver education, and interventions aimed at curbing risky alcohol consumption.